Ekstrak bonggol nanas cayenne menghambat pertumbuhan Candida albicans pada plat resin akrilik heat curing Hump extract of cayenne pineapple inhibit the growth of Candida albicans on heat cured acrylic resin plate - Prizka Brigitasari; Moh. Dharmautama (Journal of Dentomaxillofacial Science, 2013)
Hump of pineapple is one of traditional medicines found in Indonesia, containing many enzyme bromelains that canparse complex protein molecules into simpler compounds. The enzyme bromelain can inhibit the growth of Candidaalbicans. The increasing of colonies of C.albicans could be due to the increased use of denture. This study shouldexplore effectiveness of hump concentration of cayenne pineapple against C.albicans growth at 30 heat curing acrylicresin plates sized 10 x 10 x 2 mm. The plates immersed in 10 ml of C.albicans and incubated for 24 hours at 37Â°C. Theplates were divided into 6 groups, subsequently 5 acrylic resin plates, which were soaked for 8 hours at roomtemperature in an hump extract of cayenne pineapple with the concentration of 5%, 15%, 25%, 35%, and 45%.Negative control was soaked in distilled water. 0.01 ml of a 10-3dilution and dropped into the media sabouraunddextrose agar (SDA), and then incubated for 48 hours at 37Â°C, and counted the number of C.albicans colonies. Analyzed with ANOVA and LSD test, it was known a significant difference of hump extract of cayenne pineapple 5%,15%, 25%, 35%, and 45% against C.albicans growth (p <0,05). On from this fact, it was concluded that hump extractof cayenne pineapple can inhibit the growth of C.albicans, which is effective at a concentration of at least 15%.